Isolation and Genome-Based Characterization of Biocontrol Potential of Bacillus siamensis YB-1631 against Wheat Crown Rot Caused by Fusarium pseudograminearum - Qianqian Dong; Qingxiang Liu; Paul H. Goodwin; Xiaoxu Deng; Wen Xu; Mingcong Xia; Jie Zhang; Runhong Sun; Chao Wu; Qi Wang; Kun Wu; Lirong Yang (Journal of Fungi, 2023)
Fusarium crown rot (FCR) caused by Fusarium pseudograminearum is one of the most serious soil-borne diseases of wheat. Among 58 bacterial isolates from the rhizosphere soil of winter wheat seedlings, strain YB-1631 was found to have the highest in vitro antagonism to F. pseudograminearum growth. LB cell-free culture filtrates inhibited mycelial growth and conidia germination of F. pseudograminearum by 84.14% and 92.23%, respectively. The culture filtrate caused distortion and disruption of the cells. Using a face-to-face plate assay, volatile substances produced by YB-1631 inhibited F. pseudograminearum growth by 68.16%. In the greenhouse, YB-1631 reduced the incidence of FCR on wheat seedlings by 84.02% and increased root and shoot fresh weights by 20.94% and 9.63%, respectively. YB-1631 was identified as Bacillus siamensis based on the gyrB sequence and average nucleotide identity of the complete genome. The complete genome was 4,090,312 bp with 4357 genes and 45.92% GC content. In the genome, genes were identified for root colonization, including those for chemotaxis and biofilm production, genes for plant growth promotion, including those for phytohormones and nutrient assimilation, and genes for biocontrol activity, including those for siderophores, extracellular hydrolase, volatiles, nonribosomal peptides, polyketide antibiotics, and elicitors of induced systemic resistance. In vitro production of siderophore, β-1, 3-glucanase, amylase, protease, cellulase, phosphorus solubilization, and indole acetic acid were detected. Bacillus siamensis YB-1631 appears to have significant potential in promoting wheat growth and controlling wheat FCR caused by F. pseudograminearum.